0800 Posttraumatic Stress Disorder and REM Sleep Without Atonia in Veterans. (27th May 2020) - Lee, E; Yoon, I; Choi, H
Abstract: Introduction: In veterans, the prevalence of rapid eye movement (REM) sleep behavior disorder(RBD) is higher than the general population, and there is some evidence that this is related to posttraumatic stress disorder(PTSD). In addition, trauma related nightmares (TRNs) interfere with REM sleep and are often accompanied by motor activity. (rem sleep without atonia; RSWA). The purpose of this study is to determine whether the frequency of dream enactment behavior(DEB) and RSWA is different according to the presence of PTSD or trauma. Methods: The patients (n = 2262) who underwent video assisted polysomnography (PSG) and sleep-related questionnaire surveys at Veteran Health Service Medical Center in Republic of Korea were reviewed retrospectively and cross-sectionally. Based on patients diagnosed with PTSD (N = 20; 100% male; 67.9 ± 8.5 years of age), those exposed to trauma but not diagnosed with PTSD (N = 23; 100% male; age 64.0 ± 13.4) and trauma unexposed controls (N = 21; 100% male; age 59.86 ± 10.9) were matched. Results: In the PTSD group, patients who reported self-reported DEB tended to be more than the traumatic exposure group and the control group (P = 0.022). In-lab video assisted PSG showed no differences in DEB between the three groups, but RSWA. (p = 0.026) After adjusting for age, hypnotics, apnea hypopnea index (AHI), Beck depression inventory (BDI), and periodic limb movement (PLM) arousal factors, RSWA was significantly higher in the PTSD group than in the traumatic exposure group. (p = 0.006) Conclusion: The result that RSWA was significantly higher in the PTSD group than in the traumatic exposure group suggests that there may be an associated pathophysiology between PTSD and RBD. Longitudinal studies are needed to establish the link between RBD with PTSD and neurodegenerative diseases associated with synucleinopathy. Support: This study was supported by a VHS Medical Center Research Grant, Republic of Korea. (grant number: VHSMC 19033)